1999
DOI: 10.1136/bmj.318.7179.302
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety and depressive illness and help seeking behaviour in African Caribbeans and white Europeans: two phase general population survey   Commentary: Counting heads may mask cultural and social factors

Abstract: Objective To determine the prevalence of common mental disorders (anxiety and depression) and help seeking behaviour in African Caribbeans and white Europeans. Design Two phase survey in a general population sample. The first phase comprised screening with the 12 item general health questionnaire; the second phase was standardised psychiatric assessment and interview about help seeking. Setting People registered with four general practices in central Manchester. Participants Of 1467 people randomly selected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 15 publications
0
58
0
2
Order By: Relevance
“…A similar orientation emerges among employees with low selfefficacy (Gist & Mitchell, 1992) and those who are externally rather than internally controlled (Weiss & Sherman, 1973). In addition, for employees high in neuroticism, negative feedback is a source of stress and anxiety (Muris, Roelofs, Rassin, Franken, & Mayer, 2005;Shaw, Creed, Tomenson, Riste, & Cruickshank, 1999). Ultimately, for employees who are not challenge oriented and who may be somewhat threat oriented, equity is restored primarily through decreased rather than increased contribution.…”
Section: Moderators Of Envy's Effectsmentioning
confidence: 89%
“…A similar orientation emerges among employees with low selfefficacy (Gist & Mitchell, 1992) and those who are externally rather than internally controlled (Weiss & Sherman, 1973). In addition, for employees high in neuroticism, negative feedback is a source of stress and anxiety (Muris, Roelofs, Rassin, Franken, & Mayer, 2005;Shaw, Creed, Tomenson, Riste, & Cruickshank, 1999). Ultimately, for employees who are not challenge oriented and who may be somewhat threat oriented, equity is restored primarily through decreased rather than increased contribution.…”
Section: Moderators Of Envy's Effectsmentioning
confidence: 89%
“…Sociodemographic characteristics are also associated with help-seeking, with men more reluctant than women to seek formal help [18]. Ethnic differences have also been found with Asians tending to present less frequently in primary care settings even when controlling for severity [18] and GPs being less good at detecting the mental health problems of black Caribbean people [20]. People with diagnoses of depression have been found to be most likely to seek formal help compared with other mental disorders [18].…”
Section: Introductionmentioning
confidence: 87%
“…Studies conducted in England reported higher depressive symptoms (Nazroo, 1997) and depressive disorders (Shaw et al, 1999) among Caribbean immigrants compared to the general population. A study examining depression rates among Black women in the Washington, DC area found lower rates of depression among Caribbean-born women compared to their U.S.-born counterparts (Miranda, Siddique, Belin, & Kohn-Wood, 2005).…”
Section: Race Ethnicity and Depressive Symptomsmentioning
confidence: 96%
“…Finally, a national study that included a small sample of Caribbean Blacks found that they reported higher levels of stress and psychological distress than native-born Blacks . Unfortunately, findings from these studies have limited generalizability to Blacks in the U.S. due to small sample sizes and a focus on specific geographic locations (Miranda et al, 2005) and international (foreign) contexts (Nazroo, 1997;Shaw et al, 1999).…”
Section: Race Ethnicity and Depressive Symptomsmentioning
confidence: 99%